Qualitative content analysis of sharps management practices in Hce’s in Malaysia: employee factor - Abdullah Suhaimi, Afiza; Samsuddin, Niza; A. Rahman, Nor Azlina; Cheng, Jack Kie; Yusof, Muhammad Zubir (Science & Engineering Research Support Society (SERSC), 2020)
Background: Healthcare Establishment facilities in Malaysia have increased over the years. Malaysia are forwarding to global recognition as the world class health tourism destination. However, the progress of the health tourism industry in Malaysia is not only caused by the availability of hospital facilities, advanced health technologies and expertise of the doctor, but other aspects for example the role of the Healthcare Workers (HCWs) S to ensure the safety standards and practices were implemented at each Healthcare Establishments (HCEs) is a must to sustain the profile. The role of HCWs to ensure the safety standards and practices were implemented is crucial due to the high risk of becoming infected with HBV, HCV and HIV. Epidemiological studies indicates that a person who experience one needle stick injury from a needle used on an infected source patient has a risks of 30%, 1.8%, 0.3% respectively of becoming infected with HBV, HCV and HIV. Hence, this present study aimed to seek the current practices of sharp management in HCEs as a basis to implementa comprehensive, effective and safe management of sharps in order to reduce the risk of Needle Stick Injury (NSI) among healthcare workers. Method: The study adopted an exploratory qualitative approach with thematic analysis of focus group and interview responses. The data were analysed by NVivo – pro version 11. Results: Two themes resulted from the interpretative analysis; theme A: Organizational factors and theme B; Employee factors. This paper was only report on theme B: Employee factors. Three codes that influence the cause of NSI in employee factor theme were identified from the descriptive analysis including policy and guidelines, training, technology, and reporting problems and practice among the employee. Conclusion: It was then concluded that all factors responsible for the above result should be addressed by occupational health, infection prevention team, service managers and national decision makers in roll out to improve the current sharp management and practices among HCWs for the safe workplace and environment.